Suavização da curva de carga elétrica usando armazenamento geotérmico para climatização residencial e comercial - Pires, Jairo Afonso Freitas (2021)
Air conditioning has a growing participation in electricity consumption in Brazil and worldwide. It presents the possibility of storage in moments of generation of energy surplus or low thermal load. This possibility can be very useful for removing loads at times of peak demand, providing smoothing of the electrical load curve at any time, especially during peak hours. This master's dissertation presents a methodology for measuring the thermal conductivity of soil by using a window-type air conditioner adapted for this and its respective results. This research used a plate heat exchanger to replace the condenser coil of a window-type air conditioner adapted to heat flow measurement. Initially, the soil was cooled for a while, waiting for it to return to the previous temperature to start a new cycle. This process was called thermal pulse. Later, thermo-accumulation tests were carried out, when the soil was cooled with the simulation of scenarios of availability of excess energy generated by photovoltaic sources and/or with low thermal load for later recovery during peak hours. The equations of the curves generated by these processes were obtained and adapted to simulate the calculated load in a test room of the prototype house, located in geothermal site 1, of CEESP-UFSM. It was concluded that the short duration thermal pulses have greater heat recovery and that they are sufficient to acclimatize the test room during the duration of peak hours. Heat exchange is more efficient after thermo-accumulation cycles and no soil thermal saturation was observed. The inactivation time after each cycle was enough to maintain the same level of efficiency in the geothermal heat exchange. This situation is very promising for acclimatization whith the use of geothermal energy, as it allows the dimensioning of smaller heat exchangers or use in larger areas. The impact of a exchanger’s downtime or the thermo-accumulation time on it are challengin issues, and it is advisable to conduct longer tests and extend the results to the other geothermal sites.